Wild Edible Mushrooms Traded in Traditional Markets of Kerinci, Indonesia - Dalli Yulio Saputra (Jurnal Hutan dan Masyarakat, 2026)
Kerinci Regency, Jambi Province, is inhabited by the Kerinci people, recognized as one of the oldest ethnic groups in the world, and is surrounded by the forests of Kerinci Seblat National Park (TNKS). This ecological setting supports the availability of wild edible mushrooms traditionally utilized by local communities. However, scientific documentation of wild edible mushrooms traded in traditional markets has not yet been reported. This study aimed to identify wild edible mushroom species traded in traditional markets of Kerinci Regency and to document their utilization. The study was conducted in August 2024 across five traditional markets using a descriptive survey with an ethnomycological approach. Data were collected through observation, sampling, macroscopic identification, and interviews. Ten Basidiomycota species were recorded, including Polyporus sp., Auricularia sp1., Auricularia sp2., Schizophyllum commune, Lentinus sp., Lentinus squarrosulus, Pleurotus ostreatus, Pholiota sp., Lentinula cf. lateritia, and Laetiporus sulphureus. All species were traded in fresh form and consumed according to local culinary preferences.